Nilai Pendidikan Anak pada Cerita Rakyat “Tegasu Malei” Masyarakat Buton Provinsi Sulawesi Tenggara - Marwah Marwah; Henny Henny; Siti Misra Susanti (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this research is for describe educational value about folklore 'Tegasu Malei' butonese. south east sulawesi province. This research us a qualitative method. From the result of this research show us the value of education in a folklore 'Tegasu Malei' butonese, Including: a.) Moral value consisting of obedience value, honest value, humble value, ungodly value, bad value, selfish value, steal value. b.) religious value consisting of the prayer value and resignation value. c.) social value consisting of justice value, affection value, helping each other value, devotion value, and caring value also. d.) Heroic value consisting of self sacrifice value, unyielsing value, keeping promise value, and loyal friend value.